FKP Visualization Floor Plan System - Siti Nurulaini , Abdul Nasir (UTeM, 2008)
The system developed for Projek Sarjana Muda (pSM) is entitled FKP Visualization Floor Plan System which is a web based system that can view the position of lecturer room, laboratory, technician room, store, staff room and etc.The user, especially students can search the lecturer' s room based on the floor plan. It can search by lecturer's name. Besides that, it is easier for the students and lecturers to search the lecturer room and it can view a position of lecturer room in the map. With this system, users will get the information about the location in the faculty. It should interest the users to search the location of the whole faculty very easily. Then, the users only choose what place they need to know such as the laboratory. The administrator can maintain this system with edit, update and delete staff and facilities. It can help the system more interactive and suitable to use to user because the interesting interface and user friendly can attract the lecturer, staff and student to use the system. Besides, they also can register a new staff and facilities. The administrator generate a report of lecturers in the faculty and statistics of lecturer who take study leave whether they active or not. Hopefully, FKP Visualization Floor Plan System capable to help users to search the location easily.